Antiplatelet Therapy and Adverse Hematologic Events During Heart Mate II Support. (January 2016) - Saeed, Omar; Shah, Aman; Kargoli, Faraj; Madan, Shivank; Levin, Allison P.; Patel, Snehal R.; Jermyn, Rita; Guerrero, Cesar; Nguyen, Jenni; Sims, Daniel B.; Shin, Julia; D'Alessandro, David; et al.
Abstract : Background — : Hematologic adverse events are common during continuous flow left ventricular assist device support; yet, their relation to antiplatelet therapy, including aspirin (ASA) dosing, is uncertain. Methods and Results—: A single-center retrospective review of all patients supported by a continuous flow left ventricular assist device (Heart Mate II) from June 2006 to November 2014 was conducted. Patients were categorized into 3 groups: (1) ASA 81 mg+dipyridamole 75 mg daily (n=26) with a target international normalized ratio (INR) of 2 to 3 from June 2006 to August 2009; (2) ASA 81 mg daily (n=18) from September 2009 to August 2011 with a target INR of 1.5 to 2; and (3) ASA 325 mg daily from September 2011 to November 2014 with a target INR of 2 to 3 (n=70). Hemorrhagic and thrombotic outcomes were retrieved ⩽365 days after implantation. Cumulative survival free from adverse events was calculated using Kaplan–Meier curves and Cox proportional hazard ratios were generated. Hemorrhagic events occurred in 6 patients on ASA 81 mg+dipyridamole (26%; 0.42 events per patient year; mean INR at event, 2.2), 4 patients on ASA 81 mg (22%; 0.38 events per patient year; mean INR at event, 2.0), and in 38 patients on ASA 325 mg (54%; 1.4 events per patient year; mean INR at event, 2.2); P =0.004. Patients on ASA 325 mg had a higher adjusted hazard ratio of 2.9 (95% confidence interval, 1.2–7.0 versus ASA 81 mg+dipyridamole; P =0.02) and 3.4 (95% confidence interval, 1.2–9.5 versus ASA 81 mg; P =0.02) for hemorrhagic events. Thrombotic events rates were not different between groups. Conclusions—: High-dose ASA in Heart Mate II patients treated concomitantly with warfarin is associated with an increased hazard of bleeding but does not reduce thrombotic events. Abstract : Supplemental Digital Content is available in the text.